IMPLEMENTASI KEBIJAKAN TRANSPORTASI PUBLIK DALAM MENGATASI KEMACETAN DAN KEPADATAN LALU LINTAS DI MEDAN - Suci Ramadhani Siregar; Wardaya Wardaya; Darmawan Tas’an (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this reserach is to find the alternative policy that should be taken by the Medan City Government, describes the causes of traffic density and traffic congestion and to evaluate the implementation of the Medan City Government policy in facing the problems of transportation and traffic congestion of Medan City. The study was conducted at (a) the inner city corridor road: Jalan Mohd. Yamin and Jalan Balai Kota (b) outter corridor road: Jalan Yos Sudarso, Jalan Letda Sujono, Jalan Jamin Ginting, Jalan S.M. Raja, and Jalan Gatot Subroto (c) the outer ring road is Jalan Karya Jasa. Data collection from various sources and processed for analysis and evaluation using Analytic Hierarchy Process (AHP). The sample is taken by purposive way where the selected respondent has competence in reviewing policy to resolve traffic jam. Based on research results, the density and traffic congestion can be resolve with more effective transportation policy, consistent enforcement of rules by the policy implementers and public awareness to obey the rules of transportation policy that have been made.